Perancangan Website untuk Desa Mayangan sebagai Media Informasi dan Promosi - Moch Shulthoni; Ahmad Roziq; Nur Hisamuddin; Lilis Yuliati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
The tourism sector is one of the potential sectors to be developed in modern times, but not all tourist attractions can develop well. One of the factors that cause tourist attractions is the lack of promotion or delivery of information to tourists. The development of the internet is now increasingly advanced so that it is widely used by tourist site managers as a medium of information and promotion. Mayangan Village, Gumukmas District, Jember Regency has the potential to further develop. For this reason, it is necessary to take advantage of the internet by designing the Mayangan village website as a medium for information and promotion. The purpose of this service is to provide knowledge and ability of village officials in managing the Mayangan Village website. The method used is to provide education, training and assistance to create a Mayangan Village Government Website on a continuous basis. The result of this service is designing a website using data collection techniques in the form of interviews, observations, and literature studies. While the software used in designing the Mayangan Village website uses XAMPP, DreamweaverCS 5.5, Adobe Photoshop Photoshop5 and uses programming languages such as HTML, PHP, CSS, Java Script, and JQuery. The implementation of this website is accompanied by blackbox testing. In addition, the website of Mayangan Village, Gumukmas District, Jember Regency was created to inform various natural resources that can be used as tourist destinations. The information presented is expected to make it easier for people to travel. This website is expected to help increase the tourism promotion of Mayangan Village so that it can develop.